READY, STUDY, SHARE: AN INQUIRY INTO THE DIDACTIC APPROACH OF GAMIFICATION WITH A SPECIAL VIEW TO THE POSSIBLE APPLICATION IN HIGHER EDUCATION - Biro, Gabor Istvan (European Scientific Journal, ESJ, 2013)
In this article i study gamification as a didactical method and the possible application of gamification theory in higher education. Recently it became important to create a scientific basis of gamification in order to be able to differenciate between the various approaches and interpretations as the general concept started to diversify in the last two years. Gamification is also seen as a new marketing tool (Zichermann, 2010), a new trait of the employee in the 21st century (McGonigal, 2011), and a method to reach a higher level of motivation and engagement in the workplace (Zichermann, 2011) or at the school (Kapp, 2012). Unfortunately these theories handle gamification as a completely new phenomena and do not try to make a comprehension with previous didactical methodologies or concepts. This article intends to map the theory of gamification in a didactic approach by making comparison with other didactical theories, and put some remarks regarding the similarities and the differences of the concepts which will help to dispose gamification on the canvas of science. The article also address the current pedagogical situation in higher education with a special view to the most significant tendencies and analyse how the application of gamification would affect the problems and conflicts induced by them. The article concludes by framing possible directions to study the application of gamification theory in higher education and suggest to research these topics intensely.